The impact of Caesarean delivery mode towards brain and neurodevelopment among children - Tjhin Wiguna; Levina Chandra Khoe (World Nutrition Journal, 2020)
In regards to the rising rate of Caesarean birth globally, there is concern about the risk of Caesarean birth in children. However, the effect of Caesarean delivery towards the child brain and neurodevelopment is not well understood. We reviewed articles from online database with topics related to the relation between caesarean delivery mode and brain development/neurodevelopment/behaviour and emotional development. Several studies discussed how birth mode could affect brain structural connectivity through neural and hormone changes. Some studies also assessed possible effect on child’s psychological development.  The result showed differences in child’s brain development between caesarean and natural delivery in the early life, but not in the long run. Additionally, no significant association between birth mode and emotional problem.